Grow - Platt, Cynthia; Holden, Olivia (Mankato, Minnesota : Amicus Ink, 2018)
Can one little girl transform a neighborhood? With a seed of an idea and helping hands from neighbors, a girl's dream to clean up an abandoned city lot grows into something much larger. Cynthia Platt's light prose is brought to life by artist Olivia Holden's beautiful pastels in this inspiring story of hope and community.
Keywords: Children's stories, English; English fiction; Neigborhoods -- Fiction